ANALISIS KUALITAS PELAYANAN KESEHATAN PADA RSUD KETILENG KOTA SEMARANG - Obisadik, Arief Rahmat; Dwimawanti, Ida Hayu; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2015)
Health services is a concept that used in providing health services to the community. Regional Public Hospital Ketileng Semarang as a government agency in charge of providing health services is always required to work optimally in serving the community. The service is called quality if it has met the indicators that used as a barometer of the extent to which the service has done well. This study aims to determine the quality of health services in Regional Public Hospital Ketileng Semarang through service activities, inhibiting factors of service, and the driving factors of service from internal customer’s perspective (staffs) as well as through the five dimensions of service quality ( ServQual ) from Parasuraman In this study, the researcher use a qualitative method with descriptive approach. A qualitative approach with in-depth interviews toward 6 informants with election technique by accidental sampling. The results showed that from the five dimensions of service quality that described by Parasuraman, that is tangible, realibility, responsiveness, assurance, and empathy, only assurance dimension that can be said to have been carried out properly The advice that given is (1 ) increasing the number of employees in serving ( 2 ) closer scrutiny for employees ( 3 ) provide information as simple as possible in order to be understood by all patients ( 4 ) time of service is adapted with the patient visits.